Tanggung Jawab Notaris Dalam Pelanggaran Kode Etik Notaris - Latifah Latifah (Officium Notarium, 2021)
Violations committed by Notary related to the code of ethics are actions that need to be followed up and monitored by the Notary Honorary Council, so that in the future there will be no more violations and so that the level of discipline will increase and become an example for new Notaries. In addition, the role of the Notary Honorary Council as a supervisor and providing sanctions for violations to Notaries is still lacking because in practice the Honorary Council still has to coordinate with the Notary Supervisory Council to impose sanctions. Therefore, an interesting problem arises, first, what is the risk borne by a notary if there is a violation of the code of ethics? Second, how is the implementation of the sanctions imposed by the Notary Honorary Council against a notary who is proven to have violated the code of ethics? This research is an empirical juridical research using a statutory and conceptual approach. The results of this study conclude that, first, notaries who violate the Notary Code of Ethics can be subject to ethical sanctions from the Notary Honorary Council. Second, the Notary Honorary Council must continue to coordinate with the Notary Supervisory Council in imposing ethical sanctions and notaries who are subject to ethical sanctions can file an appeal.Keywords: Code of ethics; notary; responsibility; violationAbstrakPelanggaran yang dilakukan Notaris terkait kode etik adalah perbuatan yang perlu ditindak lanjuti dan di awasi oleh Dewan Kehormatan Notaris, agar kedepannya tidak terjadi kembali pelanggaran dan sehingga tingkat kedisplinan semakin meningkat dan menjadi contoh untuk notaris baru. Selain itu, peran Dewan Kehormatan Notaris juga sebagai pengawas dan memberikan sanksi atas pelanggaran kepada Notaris masih kurang karena pada praktiknya Dewan Kehormatan masih harus berkoordinasi pada Majelis Pengawas Notaris untuk menjatuhkan sanksi. Oleh karena itu timbul permasalahan menarik, pertama, bagaimana risiko yang dipikul notaris jika terjadi pelanggaran kode etik? Kedua, bagaimana pelaksanaan sanksi yang dijatuhkan oleh Dewan Kehormatan Notaris terhadap notaris yang terbukti melakukan pelanggaran kode etik? Penelitian ini merupakan penelitian yuridis empiris dengan menggunakan metode pendekatan perundang-undangan dan konseptual. Hasil dalam penelitian ini menyimpulkan, pertama, notaris yang melanggar Kode Etik Notaris dapat dijatuhi sanksi etik dari Dewan Kehormatan Notaris. Kedua, Dewan Kehormatan Notaris harus tetap berkoodinasi dengan Majelis Pengawas Notaris dalam menjatuhkan sanksi etik dan notaris yang dijatuhi sanksi etik dapat mengajukan banding.Kata Kunci: Kode etik; notaris; pelanggaran; tanggung jawab